Retrospective study on the tutorial plan in the course of complete denture of a school of dentistry - Alvarado-Menacho, Sergio (2016)
Objective: Determine the relationship between the tutoring program in the course of full denture and academic performance of the students of a school of dentistry. Materials and method: The study population were students of the seventh cycle of the school of den-tistry of the San Martín de Porres University, enrolled in the course of full prosthesis tutoring program. Five tutorial sessions were needed to meet the academic needs of learning, the most requested sessions were the theoretical 85% (±14,64) the practices were less frequent (14,22 % ±14,64). Results: There was no significant difference by gender. Students who attended the educational psychology service approved 71,55% (±18,56). Conclusions: The tutoring program was beneficial since academic performance improved. Unap-proved students were of both genders, most presented academic deficiency and behavioral problems. Increased assistance to the theoretical sessions that practices it was observed. Students who attended the educational psychology department, obtained high approval rating, but some failed the course. It is recommended to continue these studies.